WILL THE RATINGS AND REVIEWS OF ONLINE DIETARY SUPPLEMENT SCREEN FOR UNSAFE PRODUCTS IN THE E-MARKETPLACE - Benjawan, Sirikanlaya; Sratthaphut, Lawan; Poompruek, Panoopat; Kapol, Nattiya (Thai Bulletin of Pharmaceutical Sciences, 2021)
The dietary supplement market has been growing rapidly, resulting in an increased risk of consuming unsafe products. Therefore, it is important to separate unsafe products from available products. The objective of this cross-sectional study was to determine the relationship of consumer opinions towards unsafe online dietary supplement, which was shown as product ratings and product reviews. The lists of products from the health product contamination examination reports from 2016 to 2018 were applied as reference products. The available products in the e-marketplaces (LAZADA and Shopee) and their ratings and reviews between October to December 2019 have been collected and divided into 2 groups: safe and unsafe products according to reference products. Product rating was analysed by t-test whereas, product reviews were analyzed by sentiment analysis and principal component analysis (PCA). Consequently, 46 products with 288 ratings and 496 reviews were analysed. The results showed that there was no statistically significant difference in product rating between safe and unsafe products (p-value = 0.471). The reviews were classified based on marketing mix (product, price, place, and promotion) and polarity (positive, neutral, and negative). The reviews related to product and price aspects in the unsafe product group were higher than the other group. The proportion of negative reviews in the unsafe product group was higher than the other group. The result was found that product reviews of safe and unsafe product groups cannot be separated. In conclusion, There was no relationship between consumer opinions and unsafe online dietary supplements. Therefore, the consideration of product ratings and product reviews cannot be used to screen unsafe products from any available products.